Aerothermal optimisation of novel cooling schemes for high pressure components using combined theoretical, numerical and experimental techniques - Kirollos, B (2015)
The continuing maturation of metal laser-sintering technology has presented the opportunity to de-risk the engine design process by experimentally down-selecting high pressure nozzle guide vane (HPNGV) cooling designs using laboratory tests of laser-sintered—instead of cast—parts to assess thermal performance. Such tests are very promising as a reliable predictor of the thermal-paint-engine-test, which is used during certification to validate cooling system designs. In this thesis, conventionally cast and laser-sintered parts are compared in back-to-back experimental tests at engine-representative conditions over a range of coolant mass flow rates. Tests were performed in the University of Oxford Annular Sector Heat Transfer Facility. The aerothermal performance of the cast and laser-sintered parts is shown to be very similar, demonstrating the utility of laser-sintered parts for preliminary engine thermal assessments. It can be shown that in most situations counter-current heat exchanger arrangements outperform co-current arrangements. This concept, though familiar in the heat exchanger community, has not yet been applied to hot-section gas turbine cooling. In this thesis, the performance benefit of novel reverse-pass cooling systems—that is, systems in which the internal coolant flows substantially in the opposite direction to the mainstream flow—is demonstrated numerically and experimentally in film-cooled HPNGVs. It is shown numerically that reverse-pass cooling systems always act to flatten lateral wall temperature variation and to reduce peak metal temperature by maximising internal convective cooling at the point of minimum film cooling effectiveness. Reverse-pass cooling systems therefore require less coolant than other internal flow arrangements to maintain acceptable metal temperatures. The benefits of reverse-pass cooling can be fully realised in systems with long, undisturbed surface length, such as the suction-side (SS) of a HPNGV, afterburner liners, HPNGV platforms, and combustor liners. Three engine-scale HPNGVs with SS reverse-pass cooling systems were subsequently designed using bespoke numerical conjugate heat transfer and aerodynamic models to satisfy engine-realistic aerothermal and manufacturing constraints. The reverse-pass HPNGVs were metal laser-sintered and tested in back-to-back experiments with conventionally cooled HPNGVs in the Annular Sector Heat Transfer Facility. The reverse-pass HPNGVs are shown to reduce peak engine metal temperature by 30 K and reduce mean SS engine metal temperature by 60 K compared to conventionally cooled HPNGVs with the same cooling mass flow. A physically-based infra-red thermography procedure was implemented which takes into account the transmittance of the external optics, the surface emissivity of the object, the black-body temperature-radiometric characteristics of the camera, and the time-varying surrounding radiance. Failure to account for surrounding radiance is shown to result in an absolute error in overall cooling effectiveness of 0.05. A new experimental facility—the Coolant Capacity Rig—was developed in order to measure row-by-row, compartmental and total coolant capacity of HPNGVs to a precision of 0.03%, over a large range of pressure ratios and mass flows using a differential mass flow measurement technique, bypass system, and calibrated mass flow orifice. A novel method for estimating internal loss coefficients from the coolant capacity measurements has been devised which, uniquely, does not require internal pressure measurement.